Short-course performance variation across all race sections: How 100 and 200 m elite male swimmers progress between rounds - Cuenca-Fernández, F.; Ruiz-Navarro, J. J.; Polach, M.; Arellano, P.; Born, D. P. (Frontiers in Sports and Active Living, 2023)
Introduction: To investigate performance variation in all race sections, i.e., start, clean swimming, and turns, of elite short-course races for all swimming strokes and to determine the effect of performance variation on race results.